2016
DOI: 10.4067/s0718-95162016005000043
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of efficient phosphate solubilizing bacteria capable of enhancing tomato plant growth

Abstract: Phosphorus is one of the three macronutrients that are essential for plant growth and development. Inorganic phosphorus (P), which can make up to 70% of the total P content in soils, can exist in calcium-, aluminum-, or iron-complexed forms that are unavailable for plant use. As a result, mineral phosphorus, P 2 O 5 , is often used as a fertilizer to supplement the nutrient for crop growth. To reduce the addition of mineral phosphorus to agricultural soils, research in naturally occurring phosphate-solubilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 20 publications
6
70
0
12
Order By: Relevance
“…Micro‐organisms including Serratia , Enterobacter (Malleswari and Bagyanarayana ), Kluyvera (Hariprasad and Niranjana ) and Pantoea species (Sharon et al . ) were previously reported as phosphate solubilizers, consistent with this study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Micro‐organisms including Serratia , Enterobacter (Malleswari and Bagyanarayana ), Kluyvera (Hariprasad and Niranjana ) and Pantoea species (Sharon et al . ) were previously reported as phosphate solubilizers, consistent with this study.…”
Section: Discussionsupporting
confidence: 93%
“…The difference could be due to differences in the makeup of the rhizospheric communities among various plant species. Micro-organisms including Serratia, Enterobacter (Malleswari and Bagyanarayana 2013), Kluyvera (Hariprasad and Niranjana 2009) and Pantoea species (Sharon et al 2016) were previously reported as phosphate solubilizers, consistent with this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This resulted in the formation of clear zones on the agar plate with the addition of acetic acid or propionic acid, but not butyric acid ( Figure 1D). These results suggest that CaP can be degraded by acetic acid and propionic acid in the media of glucose fermentation of C. acnes [52][53][54].…”
Section: Acnes Fermentation and Cap Solubilization By Fermentationmentioning
confidence: 99%
“…This resulted in the formation of clear zones on the agar plate with the addition of acetic acid or propionic acid, but not butyric acid ( Figure 1D). These results suggest that CaP can be degraded by acetic acid and propionic acid in the media of glucose fermentation of C. acnes [52][53][54]. The CaP deposits and increased level of IL-6 in skin and blood are the major manifestations observed in CKD patients undergoing dialysis [42,55,56].…”
Section: Regulation Of Cap-induced Il-6 and Histone H3 Lysine 9 Acetymentioning
confidence: 99%